Urgensi Diklat Berjenjang Tingkat Dasar Pendidik Pada Peningkatan Kompetensi Guru Raudlatul Athfal Bekerjasama dengan IGRA dan Himpaudi Kabupaten Pasuruan - Luluk Rochanah (SELING: Jurnal Program Studi PGRA, 2019)
This research aims a). Knowing the importance of basic level tiered education and training in the competence of Raudlatul Athfal educators in Pasuruan Regency b). Knowing how to apply tiered education at Basic Level RA Educators in Pasuruan c). Knowing the quality of educators in aligning behavioral attitudes after attending basic level tiered training. This study uses a qualitative approach that uses an approach based on a phenomenological perspective. The analysis was conducted with a phenomenological approach, observation and self-report. The collected data is identified based on the three components of Developmental Appropriateness Practices (DAP). This research concludes that the quality of teachers cannot be beaten by the education system in influencing the quality of education in other words, no matter how good the education system is, if not followed by good teacher quality, the quality cannot be maximally improved, basic level tiered education is one of coaching or improvement Educator competence, seen in the results of the Tiered Education and Training activities, namely (1) many Raudlatul Athfal teachers who do not understand the learning methods to be applied to teaching and learning activities of young children after attending a tiered education, the Raudlatul Athal teacher better understands the methods to be applied to the learning activities of children (2) basic level tiered education and training activities can add knowledge about early childhood knowledge (3) Raudlatul Athfal teacher can arrange management and learning tools perfectly from planning, implementation, observation to ev the teacher's aluasion can compile well (4) the material that has been given in basic level tiered education and training is very suitable with the problems and needs experienced by the teacher of Raudlatul Athfal